A Case Report of a Prenatally Missed Mowat-Wilson Syndrome With Isolated Corpus Callosum Agenesis. (22nd April 2021) - Şenbil, Nesrin; Arslan, Zeynep; Sayın Kocakap, Derya Beyza; Bilgili, Yasemin
Mowat–Wilson syndrome (MWS) is an autosomal dominant genetic disorder caused by ZEB2 gene mutations, manifesting with unique facial characteristics, moderate to severe intellectual problems, and congenital malformations as Hirschsprung disease, genital and ophthalmological anomalies, and congenital cardiac anomalies. Herein, a case of 1-year-old boy with isolated agenesis of corpus callosum (IACC) in the prenatal period is presented. He was admitted postnatally with Hirschsprung disease (HSCR), hypertelorism, uplifted earlobes, deeply set eyes, frontal bossing, oval-shaped nasal tip, ''M'' shaped upper lip, opened mouth and prominent chin, and developmental delay. Hence, MWS was primarily considered and confirmed by the ZEB2 gene mutation analysis. His karyotype was normal. He had a history of having a prenatally terminated brother with similar features. Antenatally detected IACC should prompt a detailed investigation including karyotype and microarray; even if they are normal then whole exome sequencing (WES) should be done.